2014
DOI: 10.1002/ana.24083
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus encephalitis is a trigger of brain autoimmunity

Abstract: In five prospectively diagnosed patients with relapsing post-herpes simplex encephalitis (HSE), NMDAR-antibodies were identified. Antibody synthesis started 1–4 weeks post-HSE, preceding the neurological relapse. Three of five patients improved post-immunotherapy, one spontaneously, and one has started to improve. Two additional patients with NMDAR-antibodies, 9 with unknown neuronal surface-antibodies, and one with NMDAR and unknown antibodies were identified during retrospective assessment of 34 HSE-patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
308
1
23

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 393 publications
(351 citation statements)
references
References 20 publications
13
308
1
23
Order By: Relevance
“…Second, it is of potential etiological interest that NR1‐specific B cells were efficiently expanded in vitro by toll‐like receptor agonism because this is an established property of herpes simplex virus (HSV),26 and HSV is both a known trigger of classical NMDAR‐antibody encephalitis,27, 28 and of NR1‐IgG and NR1‐IgM generation in patients without typical clinical features of NMDAR‐antibody encephalitis 21, 29. However, this hypothesis would necessitate preformed NR1‐reactive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is of potential etiological interest that NR1‐specific B cells were efficiently expanded in vitro by toll‐like receptor agonism because this is an established property of herpes simplex virus (HSV),26 and HSV is both a known trigger of classical NMDAR‐antibody encephalitis,27, 28 and of NR1‐IgG and NR1‐IgM generation in patients without typical clinical features of NMDAR‐antibody encephalitis 21, 29. However, this hypothesis would necessitate preformed NR1‐reactive cells.…”
Section: Discussionmentioning
confidence: 99%
“…The trigger of the disease in the rest of female patients as well as in young children and male patients is largely unknown, although in some cases other tumors (such as small‐cell lung cancer2) have been identified. In a small subset of patients the anti‐NMDAR immune response is triggered by herpes simplex encephalitis 4. Irrespective of the trigger of anti‐NMDAR encephalitis, data from previous studies suggested an enhancement of the immune response within the CNS, with potential antigen‐driven affinity maturation and clonal expansion of plasma cells 16.…”
Section: Discussionmentioning
confidence: 99%
“…Encephalitis associated with anti‐ N ‐methyl‐ d ‐asparate receptor (anti‐NMDAR) antibodies (“antibodies”) can be triggered by the presence of peripheral tumors1, 2 or preceding viral CNS infection or occur in the absence of such obvious events 3, 4. It typically presents with neurocognitive deficits variably accompanied by psychiatric symptoms, epileptic seizures, and disorders of movement and consciousness.…”
Section: Introductionmentioning
confidence: 99%
“…With antiepileptic medications, steroids, plasma exchange, and intravenous immunoglobulin (IVIg), the patient improved and was discharged to skilled nursing care. Anti-NMDAR encephalitis and other immune-mediated encephalitides can be triggered by HSV [152]. In contradistinction to the initial HSVE, significant contrast enhancement on brain MRI has been observed [153], and may be a biomarker of autoimmune relapse, though future studies with greater patient numbers are needed.…”
Section: Case 2: A-79-year-old Woman In Sementioning
confidence: 99%
“…Multiple case reports and, more recently, case series have demonstrated that many patients with HSVE relapse develop anti-NMDAR immunoglobulins [152,[169][170][171][172][173][174]. Antibodies targeting other known neuronal antigens and unidentified neuronal antigens have also been reported in this setting [152,153,174,175]. The precise pathogenic mechanisms remain to be elucidated, but may involve mechanisms of molecular mimicry or an autoimmune response to the release of neuronal antigens associated with host cell lysis.…”
Section: Immune-mediated Encephalitis and Apparent Hsve Relapsementioning
confidence: 99%